2015
DOI: 10.1080/20786190.2015.1055670
|View full text |Cite
|
Sign up to set email alerts
|

A blank page: feedback from first referral hospitals to primary health care clinics

Abstract: Background: Primary care practitioners depend on the feedback from hospitals in order to care for returning patients effectively. Lack of such feedback from the hospitals leads to frustration, poor efficiency and care that it is not cost effective. This study examined the presence and adequacy of written feedback from first referral hospitals to primary health clinics (PHC) in the Metsweding district, Tshwane, South Africa. Methods: A retrospective descriptive stratified cluster study was done by reviewing 863… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…(30) In this study, we found that name& signiture of specialist recorded in (40%)feedback reports which similar to the result reported in Qassim region,were recorded in (41.8%), (30) and lower than those obtained in Southeastern Saudi Arabia, and study done in South Africa, were name & sign of specialist recorded in 89.2%,60.8% of feedback reports respectively]. (38,27) In this study we found 53% mention the plan of management; only 7% record the treatment while the remaining 46% mention (It has been making the necessary).Which is lower than the result done in South Africa, [where treatment recommendations recorded in63%]. (27) The reasons behind skipping the referral feedback notes might be related to either the doctors were overloaded or they thought it was of no use, and some did not re-send the patient to the PHCCs at all.…”
Section: Frequency Distribution Of Components Of Referral Letter and supporting
confidence: 74%
See 3 more Smart Citations
“…(30) In this study, we found that name& signiture of specialist recorded in (40%)feedback reports which similar to the result reported in Qassim region,were recorded in (41.8%), (30) and lower than those obtained in Southeastern Saudi Arabia, and study done in South Africa, were name & sign of specialist recorded in 89.2%,60.8% of feedback reports respectively]. (38,27) In this study we found 53% mention the plan of management; only 7% record the treatment while the remaining 46% mention (It has been making the necessary).Which is lower than the result done in South Africa, [where treatment recommendations recorded in63%]. (27) The reasons behind skipping the referral feedback notes might be related to either the doctors were overloaded or they thought it was of no use, and some did not re-send the patient to the PHCCs at all.…”
Section: Frequency Distribution Of Components Of Referral Letter and supporting
confidence: 74%
“…Despite this, the final diagnosis was specified in (62%) of feedback reports; This assessment was near those obtained in South Africa and in Southeastern Saudi Arabia (58.6, 66.7% respectively) . (27,38) While less than the result reported by study done in Qassim region ,were diagnosis present in (77.9%) of feedback reports. (30) In this study the investigations done at the hospitals were only recorded in (14%)of the feedback letters, and clinical finding recorded in only (4%) which were near those obtained in Asir region, Saudi Arabia,were the result obtained (21.5% ,5.9% of feedback reports, respectively), (28) In 85% of the feedback reports there were no clear recommendations from the specialists.…”
Section: Frequency Distribution Of Components Of Referral Letter and mentioning
confidence: 83%
See 2 more Smart Citations
“…Within the South African public healthcare context, such a system would be essential to the success of a universal newborn hearing screening (UNHS) programme because of the hierarchical nature (Legodi & Wolvaardt 2015) of our three-tier public health referral system. An online data management system would allow for interdisciplinary tracking along the referral pathway, where paediatric hearing screening occurs at the primary healthcare facility with referral to a secondary or tertiary healthcare facility if advanced diagnostic testing and confirmation of hearing loss is required.…”
Section: Introductionmentioning
confidence: 99%